Взаємозв’язки української інтелігенції Галичини та Наддніпрянщини у другій половині ХІХ століття - Зашкільняк, Леонід (Wydawnictwo Uniwersytetu Rzeszowskiego, 2024)
Kształtowanie się ukraińskiej narodowej idei oraz ruchu wyzwoleńczego przypadło na XIX i początek XX wieku. Odbywało się to w złożonych warunkach rozdzielenia podstawowej masy ukraińskiej ludności między dwoma imperiami – Romanowowych i Habsburgów, które wszystkimi środkami usiłowały nie dopuścić do umocnienia narodowej świadomości Ukraińców. Jednak w drugiej połowie XIX wieku nieliczne kręgi ukraińskiej inteligencji Naddnieprzańskiej Ukrainy i Galicji nawiązały wzajemną relację i rozwinęły aktywną kulturową i edukacyjną działalność wśród ukraińskiej ludności obu imperiów. W związku z represjami i prześladowaniami Ukraińców w Rosji narodowa inteligencja zadecydowała przenieść centrum życia społeczno-kulturowego do Galicji, gdzie po reformach konstytucyjnych Habsburgów z lat 60. XIX wieku zostały spełnione warunki legalnej społeczno-politycznej działalności. Konsekwencją współpracy były powołane na terenie Galicji organizacje (Towarzystwo imienia Szewczenki) i czasopisma („Diło”, „Prawda”, „Zoria”), które odegrały wiodącą rolę w podniesieniu ukraińskiego narodowego ruchu.

The formation of the modern Ukrainian national idea and the liberation movement occurred in the 19th and early 20th centuries. Their emergence and spread took place in the difficult conditions of the division of the Ukrainian population between two empires - the Romanovs and the Habsburgs, which tried by all possible means to prevent the spread of the Ukrainian national consciousness. However, in the second half of the 19th century, a few circles of the Ukrainian intelligentsia in Transdnieper Ukraine and Galicia established relations with each other and developed active cultural and educational activities among the Ukrainian population of the two empires. Due to the repression and persecution of Ukrainians in Russia, the centre of social and cultural life and the formation of national programs moved to Galicia, where after the constitutional reforms in Austria in the 1860s opportunities for legal social and political activity have developed. The result of the cooperation and interaction between the intelligentsia of Naddnipryanshchyna and Halychyna in the second half of the 19th century was the founding or strengthening of Ukrainian public cultural-educational organisations (the Shevchenko Society) and numerous periodicals (“Dilo”, “Pravda”, “Zorya” etc.) in the Galician province of Austria-Hungary, which played a leading role in the elevation of the Ukrainian national movement.
Relacje ukraińskiej inteligencji Galicji i Naddnieprzańskiej Ukrainy w drugiej połowie XIX wieku
Interrelationships of the Ukrainian intelligentsia from Galicia (Halychyna) and Transdnieper Ukraine (Naddnipryanshchyna) in the second half of the 19th century
Keywords: ukraińska idea; ukraińska inteligencja; Galicja; Naddnieprzańska Ukraina; narodowy ruch; Ukrainian concept; Ukrainian intelligentsia; Galicia; Dnieper Ukraine; national movement